The effects of psychological training on anxiety and archery performance - Bhum, D. J.; Ma, S. R.; Joo, D. Y.; Kim, J. E. (2001)
The purpose of this study is to examine the effectiveness of a psychological training for reducing the competitive state anxiety response, and the effect of psychological training on archery performance. The participants were 24 high school archers (12 male, 12 female), pre-test a Competitive State Anxiety Inventory-2 (CSAI-2) was completed, and archery performance was recorded (90m, 70m, 60m, 50m). After this pre-test, the participants were divided randomly within each sex into an experimental group (n = 12) and a control group (n = 12). The experimental group received the psychological training program for a nine week period. The program was in the form of Progressive Muscle Relaxation and Imagery (archery). The control group had no contact during the experiment period. After 9 weeks, all the measures are repeated. The following results were recorded, a significant (p < .05) reduction in CSAI-2 from pre- to post-test for the experimental group compared to the control group. ANOVA indicated significant improvement in archery performance for the experimental group compared to the control group. However, results do not support the existence of a relationship between gender and archery performance. There have only been a few studies carried out on the effects of psychology training on both physiological and psychological aspects of anxiety in sport. Future studies should not only examine the psychological aspects, but also physiological changes such as general muscle tension.